Revalence of Molar Incisor Hypomineralization among Primary School Children in Baquba City - Esam Abdulla, Saif; Hussein Awn , Baydaa (Diyala Journal of Medicine, 2024)
Background: Molar incisor hypomineralization is a clinical symptom of general hypomineralization affecting a single or multiple first permanent molars, which is generally accompanied with incisors. Objective: To determine the prevalence of molar incisor hypomineralization among 12 years students in Baquba city. Patients and Methods: This study was conducted from middle of January 2022 till the end of May 2022 in Baqubah city/Diyalla Governorate/Iraq. The sample excluded all students who had other enamel defects (fluorosis or hypoplasia, uncooperative students and students who refuse to participate. Results: Out of 700 participants, 52.43% of them were females and the rest were males. About 13% of the total sample showed a molar incisor hypomineralization, with significant association between gender, in which male were significantly more affected than females. The data showed 13% of the total sample had a demarcated opacities . Also the results showed that the upper centrals were more affected by hypominrlization than other teeth. Conclusion: However, the study revealed that demarcated opacity was the most common form of defect with a significant correlation, with a frequency of 13%. The upper central tooth was always the most commonly impacted by molar incisor hypomineralization.